PERSEPSI GAY TERHADAP STIGMATISASI GAY OLEH PETUGAS KESEHATAN - Yafi Sabila Rosyad; Wenny Savitri; Sri Purwaningsih (MEDIA ILMU KESEHATAN, 2015)
Background: The presence of gays in the community still makes heterosexual as normal sex orientation. There are unfair perceptions of heterosexual group that develop into real behaviors which are very detrimental for homosexuals group in the form of stigmatization against homosexuals. Stigmatization for gay in society also comes from health professionals when they think homosexuals conduct violation to the rule of law, social and religious values. Therefore gays tend to visit certain health care providers who are familiar with them or to hide the identity that they are homosexuals. Objective: To determine the perceptions of gays regarding gay stigmatization of health care providers. Methods: A qualitative by using snowball sampling with the total of 10 participants was applied. The Conceptual Content Cognitive Map (3CM) methods followed by interview were utilized to gather data. Results : Six themes regarding gay stigmatization of health care as perceived by gays as follows: (1) gay is a divergence and contagious; (2) being gay is normal; (3) flamboyant and hedonist personality; (4) exclusive and bad personality; (5) at high risk of sexually transmitted diseases, lack of self-control, and diseased; and (6) having good personality. Conclusion : Six themes with predominantly negative perceptions regarding stigmatization on gays by health care providers as perceived by gays describe the need of transformation of health care service to increase the quality of health of minor population like gay. Keywords : Homosexual, Perception, Stigma, Gay, and The Conceptual Content Cognitive Map (3CM)